Analysis of Needs for Development of Learning Media UNO Spin Cards Digestive System Materials for High School Students - Ridwan, Cindy Utami; Ristiono; Fitri, Rahmadhani; Ardi (Program Studi Pendidikan Biologi Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2024)
Learning media has an important role in the learning process so that students can understand the material and also be able to actively participate in the learning process. Digestive system material in humans includes material that is quite difficult for students to understand. Learning media in the form of UNO spin cards can be used as a solution to the problems of students who have difficulty understanding learning materials. The development of learning media in the form of UNO spin cards was developed referring to the IDI (Instructional Development Institute) development model which consists of three stages, namely Define, Develop, and Evalute. This learning media uses the game method in accordance with the criteria and needs of students' learning media that presents material more concisely so that it is easy to understand.